Association of prenatal exposure to cadmium with neurodevelopment in children at 2 years of age: The Japan Environment and Children's Study. (November 2021) - Ma, Chaochen; Iwai-Shimada, Miyuki; Nakayama, Shoji F.; Isobe, Tomohiko; Kobayashi, Yayoi; Tatsuta, Nozomi; Taniguchi, Yu; Sekiyama, Makiko; Michikawa, Takehiro; Yamazaki, Shin; Kamijima, Michihiro; ,
Graphical abstract: Highlights: Cadmium exposure during pregnancy may pose a neurodevelopmental risk to children. Cadmium concentrations were measured in maternal and cord blood. Child's sex, maternal smoking, and gestational diabetes modified the associations. Identification of high-risk groups is important for tailoring health interventions. Abstract: Background: Prenatal cadmium exposure has been associated with adverse neurodevelopmental outcomes. However, previous findings are contradictory, and little is known about the potential modifiers of the cadmium-related neurodevelopmental risk. We investigated the associations between prenatal cadmium exposure and neurodevelopment in 2-year-old children and examined the influence of mother/child characteristics. Methods: We recruited 3545 mother–child pairs from the Japan Environment and Children's Study. We collected maternal blood during mid/late pregnancy and cord blood at delivery, and measured cadmium concentrations using inductively coupled plasma mass spectrometry. Neurodevelopment was assessed using the Kyoto Scale of Psychological Development (KSPD), which includes cognitive-adaptive (C-A), language-social (L-S), postural-motor (P-M) and developmental quotient (DQ) domains. Associations between cadmium and KSPD scores were tested using multivariable models after controlling for confounders. Results: Median levels (interquartile ranges) of cadmium in maternal and cord blood were 0.70 (0.52–0.95) and 0.04 (0.03–0.06) μg/L, respectively. Maternal blood cadmium concentrations were inversely associated with P-M scores in boys (β = −1.4, 95% confidence interval (CI): −2.7, −0.038), DQ in children of mothers who smoked during pregnancy (β = −2.9, 95% CI: −5.7, −0.12), P-M (β = −5.4, 95% CI: −10, −0.67), C-A (β = −6.1, 95% CI: −11, −1.8), L-S (β = −9.0, 95% CI: −13, −4.8) and DQ scores (β = −6.4, 95% CI: −9.6, −3.1) in children born to mothers with gestational diabetes. Cord blood cadmium concentrations were negatively associated with L-S scores (β = −6.0., 95% CI: −11, −0.91) in children born to mothers with gestational diabetes. Conclusions: Prenatal cadmium exposure was negatively associated with neurodevelopment in boys, in children whose mothers smoked, and in children born to mothers with gestational diabetes. Further studies in other populations are needed to confirm our findings.